Perempuan dalam Kehidupan Gereja: Suatu Refleksi Antropologis tentang Manusia Diciptakan menurut Gambar Allah sebagai Makhluk Seksual - Maretio, Yehezkiel Divo (Felicitas, 2023)
One of the most interesting discussions related to Christian Anthropology is human sexuality, especially the relationship between men and women. The Church also concerns about the relationship between men and women. This is inseparable from the Church's reflection on the dignity, rights and obligations of women in various fields of society and the Church. Through this paper, the author would like to focus on the role of women in the Church, especially the Church's attitude towards the role of women. The author will look at the main basis in Christian Anthropology, namely the story of the creation of men and women.